2021
DOI: 10.1080/26895293.2021.1883126
|View full text |Cite
|
Sign up to set email alerts
|

Variation in susceptibility of Eucalyptus grandis and selected hybrid clones to two termite species Macrotermes bellicosus and M. subhyalinus in Uganda

Abstract: The maximum productivity of plantation forestry and its role in climate change mitigation, adaptation and resilience cannot be met without proper management. Termites in the genus Macrotermes have been reported as a major challenge to Eucalyptus plantation forestry establishment. The current study evaluated the susceptibility of four Eucalyptus hybrid clones: GU 7, GC 796, GC 550 and GC 796/2, and E. grandis Hill ex Maid. to the most damaging Macrotermes bellicosus (Smeathman) and Macrotermes subhyalinus (Ramb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Fajar et al, (2021), reported that termites foraged on Eucalyptus. Nakabonge & Matovu, (2021) reported that Eucalyptus species are highly susceptible to termites.…”
Section: Evaluation Of Uncrushed Feed Substratesmentioning
confidence: 99%
“…Fajar et al, (2021), reported that termites foraged on Eucalyptus. Nakabonge & Matovu, (2021) reported that Eucalyptus species are highly susceptible to termites.…”
Section: Evaluation Of Uncrushed Feed Substratesmentioning
confidence: 99%
“…The forests have a role in reducing natural disaster hazards, including oods, droughts, landslides, and other extreme events [1]. Otherwise, in the face of demands for technologies addressed to achieve the goals of sustainable development, the planted forests of Eucalyptus are the source of the broadest hardwood grown in the world because of its increasing importance for ber and energy [2,3].…”
Section: Introductionmentioning
confidence: 99%